Multiply. Express your answer as a polynomial in standard form. (1 point)

(6x−7)(6x+7)=
(
6
𝑥

7
)
(
6
𝑥
+
7
)
=

Check Answer

1 answer

To multiply the two binomials \((6x - 7)(6x + 7)\), we can use the distributive property (also known as the FOIL method for binomials):

\[ (6x - 7)(6x + 7) = 6x \cdot 6x + 6x \cdot 7 - 7 \cdot 6x - 7 \cdot 7 \]

Calculating each part:

  1. \(6x \cdot 6x = 36x^2\)
  2. \(6x \cdot 7 = 42x\)
  3. \(-7 \cdot 6x = -42x\)
  4. \(-7 \cdot 7 = -49\)

Now, combining all these terms together:

\[ 36x^2 + 42x - 42x - 49 \]

The \(42x\) and \(-42x\) cancel each other out:

\[ 36x^2 - 49 \]

So, the final answer in standard form is:

\[ \boxed{36x^2 - 49} \]